Protocol for the impact of paramedics in NHS primary care: Application of realist approaches to improve understanding and support intelligent policy and future workforce planning - Eaton, G; Williams, V; Wong, G; Roberts, N; Mahtani, K (College of Paramedics, 2019)
Introduction: In the United Kingdom, changing demands on ambulance services has caused a change in what is expected of a paramedic. As well as advanced life support, paramedics now need to be skilled in managing a range of urgent case presentations, with emphasis on treat-at-scene. The change in the scope of work paramedics can undertake has established their role within primary care. However, as paramedics transition to roles within primary care, their knowledge and skillset will undoubtedly need to change. The current opportunities for paramedics’ employment in primary care require careful evaluation. In order to contribute to patients’ and the NHS’ primary care agenda, evidence must be generated to show how and why these changes would work, for whom, in what context and to what extent.